(untitled) (Journal of Nuclear Technology in Applied Science, 2019)
The biodiversity of aquatic and terrestrial ecosystems in Egypt including seas, lakes, and soils with high salinity levels provides rich habitats for flourishing halophilic microorganisms. The present study aims to isolate halophilic bacteria from sixteen samples representing ecosystems with various geographic locations and surveying the mechanisms by which they can tolerate the osmotic stress. Results revealed the highest salinity levels; sodium, chloride, sulfate, magnesium, calcium, and potassium concentrations in water sample of Wadi El-Natroun Lake since the total number of halophilic bacteria was4.68/g and the largest number of halophilic genera was observed in the northern coast of Matrouh governorate. A total of 60 bacterial isolates selected during (June-October 2015) were screened using thin layer chromatography for osmolyte; ectoine. It has the ability to decrease the harmful effects of high salinity, heating, freezing, drying as well as oxygen radicals and other denaturing agents in halophiles. Quantitative estimation of ectoine by high-performance liquid chromatography showed its yield was ranged between 185 and 700 mg/l. Using biochemical tests and 16s rRNA technology, the most active ectoine-producers were identified as Vibrio sp. CS1 and Salinivibrio costicola SH3. The yielded ectoine was purified using cation exchange chromatography (Dowex 50 WX8 resin) and its physicochemical properties were investigated using standard methodology. Characterization of purified ectoine via nuclear magnetic resonance and fourier transform infrared spectroscopy showed the similarity between bacterial ectoine and the authentic was nearly 99%.